Systematic Literature Review of Counterproductive Work Behavior From Several Perspectives - Muhammad Takrim; Abdul Haeba Ramli; Safuan` Safuan; Edi Hamdi (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study presents a systematic literature review of counterproductive work behavior (CWB) using the PRISMA methodology to analyze research trends over the past decade (2014–2024). CWB encompasses negative actions performed by employees that may harm organizations, either directly or indirectly. This study identifies key factors influencing CWB, including personality traits such as narcissism, decision-making styles, perceived task legitimacy, and broader social and economic factors. The findings reveal that illegitimate tasks, job stress, and an unfavorable organizational environment are primary triggers of CWB. Additionally, leadership factors significantly contribute to the emergence of counterproductive behaviors in the workplace. Through an analysis of 11 selected journal articles from the Scopus database, this study highlights the trends in CWB research across various countries and industries, particularly at the managerial level. This research provides insights into the importance of organizational policies and managerial interventions in mitigating the negative impacts of CWB. It also identifies gaps in the literature, offering opportunities for further exploration, particularly in understanding the role of cultural and organizational policies in preventing CWB. By adopting a more holistic approach, organizations can foster a healthier and more productive work environment. Keywords: Counterproductive Work Behavior, Managers, Systematic Literature Review, PRISMA, Organizational Factors